In vivo evaluation of an electrospun gelatin nonwoven mat for regeneration of epithelial tissues. Issue 8 (9th April 2019) - Strassburg, Sandra; Caduc, Madeline; Stark, Gerhard Bjoern; Jedrusik, Nicole; Tomakidi, Pascal; Steinberg, Thorsten; Simunovic, Filip; Finkenzeller, Günter
Abstract: One major objective in epithelial tissue engineering is to identify a suitable biomaterial that supports epithelial tissue formation. Therefore, the purpose of this study is to elucidate a novel electrospun gelatin nonwoven mat (NWM) for epithelial tissue engineering purposes in vivo. This NWM was seeded with either human gingival keratinocytes (GK, in coculture with gingival fibroblast) or human skin epithelial keratinocytes (EK, in coculture with skin dermal fibroblasts). These constructs were ex vivo cultured for 4 days before subcutaneous implantation into athymic nude mice. After 7 days, the constructs were explanted and investigated by immunohistology. Our results show that GK form a stratified epithelium on the surface of the NWM, mostly independent of a fibroblastic counterpart. Like native mucosa, the regenerated epithelium showed expression of epidermal growth factor receptor, cytokeratin‐14 and ‐1, and involucrin. Only the expression of the basement membrane constituent laminin 5 was more pronounced in cocultures. Comparing GK and skin EK, we found that skin EK form a less developed epithelial tissue. Furthermore, the NWM allows not only for epithelial tissue formation by GK, but also for infiltration of human fibroblasts and mouse immune cells, thus representing a biomaterial with potential regenerative capacity for oral mucosa tissue engineering applications. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1605–1614, 2019.